Role of exosomes in the protection of cellular homeostasis. Issue 2 (4th March 2017) - Desdín-Micó, Gabriela; Mittelbrunn, María
ABSTRACT: Due to their ability to shuttle proteins, lipids and genetic material between distant cells, exosomes promote extensive phenotypic changes in recipient cells, modulating immune responses, cellular migration, cancer metastasis or the spreading of neurotoxic protein aggregates in neurodegenerative diseases. Besides intercellular communication, exosome biogenesis and secretion permit the rapid release of a selective repertoire of compounds, conferring cells with an additional mechanism to fight alterations in protein, lipid or RNA homeostasis during stress or pathological conditions. Here, we review the dual role of the different quality control mechanisms arising from the endolysosomal system and the diverse situations that control the decision between degradation or secretion. The crosstalk between exosome secretion and the different cellular degradation mechanisms confers an additional layer of protection to maintain cellular integrity and homeostasis in a number of physiological and pathological conditions.